The Physiological Basis of the Genetic Progress in Yield Potential of CIMMYT Spring Wheat Cultivars from 1966 to 2009 - Aisawi, K. A. B.; Reynolds, M. P.; Singh, R. P.; Foulkes, M. J. (Crop science, 2015)
ABSTRACT Our objective was to investigate the physiological basis of genetic progress in grain yield in CIMMYT spring wheat (Triticum aestivum L.) cultivars developed from 1966 to 2009 in irrigated, high‐potential conditions. Field experiments were conducted during three growing seasons in northwest Mexico (2008–2009, 2009–2010, and 2010–2011) examining 12 historic CIMMYT semidwarf spring wheat cultivars released from 1966 to 2009. The linear rate of genetic gain in grain yield was 30 kg ha−1 yr−1 (0.59% yr−1; R2 = 0.58, P = 0.01). Grain yield progress was associated with increased aboveground dry matter (AGDM) at harvest (R2 = 0.80, P < 0.001) and heavier grain weight (R2 = 0.46, P < 0.05). There was a positive linear association between AGDM and plant height (R2 = 0.43, P < 0.05) and between grain weight and the date of complete canopy senescence (CCS) among the 12 cultivars (R2 = 0.36, P < 0.05). There was no change in grains per square meter or harvest index (HI) with year of release (YoR). Grain weight was positively associated with potential grain weight (PGW), and PGW, in turn, was positively associated with rachis length per spikelet among the cultivars. Overall spike dry matter (DM) per square meter at anthesis (GS61) +7 d did not change with YoR. There was a trend for a linear increase in AGDM of fertile shoots (expressed as g m−2) at GS61 +7 d with YoR, but this was counteracted by spike partitioning decreasing overall during the 43‐yr period from 0.25 to 0.23. There was a linear increase in preanthesis flag‐leaf stomatal conductance with YoR (P < 0.05). There was no change in grain growth response to a degraining treatment imposed at GS61 +14 d (mean grain weight response +5.5%) indicating that the degree of source limitation to grain growth appeared to be small and unchanged in the older and modern cultivars. Generally, these results indicated that the rate of genetic progress in CIMMYT spring wheat has slowed but has not plateaued in recent decades, while genetic gains were associated with increase in both potential and final grain weight.